Mitigation of the Work Accident Risk on Construction Industry (International Conference of Graduate School on Sustainability (ICGSS), 2020)
Work accidents on construction industry can harm all parties involved in project activities, especially for workers because they can cause disability or even death. Work accidents can also affect the time, cost and quality of a project. The risk of work accidents can be caused by many factors. This study is to review research articles that have been previously published using a Systematic review on Interviewing Technique, Root Cause Analysis (RCA) and Fault Tree Analysis (FTA). Goals of this study is to group factors causing the potential risk of work accidents. Result of this study is the factors that cause the risk of work accidents that are divided into 4 factors, namely human factors, environmental factors, management factors and work method factors. This study is expected to help contractors in mitigating and minimizing the risk of work accidents in the construction field.